Information Literacy Using the Central Sulawesi Museum on Motivation for Learning History at SMA Labschool Untad Palu - Afni, Nur Afni (Kirana Publisher (KNPub), 2023)
The importance of information literacy learning among teachers and students has enhanced comprehension and digital media skills. Learning activity and motivation are the factors that spark a particular behavior and give it a resistant orientation that will result in tenacity and not easily cracks in reaching achievement despite many obstacles, basically having a variety of learning-related motivations. This study introduces museums to students as a learning resource to explore the function of information literacy and the desire to study student history. It is qualitative research. People will be asked to participate in interviews and observations, contributing information, opinions, and perceptions to understand the social phenomenon from the participant's perspective. The results indicated how much cultural park administrators and museums promoted using information technologies to attract visitors to educational institutions. Offering details on museum collections and exhibitions relating to historical topics might help implementers of cultural parks and museums motivate students to learn more. This is particularly beneficial for technical implementers since it helps the general public learn about museum collections through brochures, catalogs, websites for cultural parks and museums, and social media, like Instagram.